Thermal and biodegradable properties of poly(lactic acid)/ carbon-based nanocomposites - Norazlina, Hashim (2020)
Poly(lactic acid) (PLA) is a biodegradable plastic and grabs attention in several applications such as biomedical implantation, film, packaging and clothing. Unfortunately, PLA itself has brittle characteristic brings to poor mechanical properties and slow ability in degradation leads to waste disposal problem. The present research aims to develop material by using different technique of preparation that have a good combination of properties and optimum degradation ability. The PLA nanocomposites were prepared via melt and solution blending that was consisted of five different carbonbased materials, graphite (Gt), graphene oxide (GO), graphene (Gr), carbon nanotubes (CNTs) and modified CNTs (mCNTs). The effect of 5 wt.% poly (ethylene glycol) (PEG) as plasticizer on nanocomposites with carbon-based material loading at 0.5 wt.%, 1.0 wt.%, 1.5 wt.% and 2.0 wt.% were studied. The analysis of physical properties for both melt and solution blending methods were done using hardness testing and melt flow index (MFI). Neat PLA only gave around 69.0 to 77.6 Shore D in hardness test, while MFI exhibited around 36.1 to 39.4 g/10 min. PLA/mCNTs and PLA/PEG/mCNTs at 1.5 wt.% prepared by melt blending exhibited highest values of hardness testing which were 86.0 and 85.9 Shore D, respectively. In MFI study, the results were 70.0 g/10 min for PLA/mCNTs and 80.3 g/10 min for PLA/PEG/mCNTs. Result from solution blending method showed the maximum hardness values for PLA/mCNTs and PLA/PEG/mCNTs at 2.0 wt.% nanofiller loading, 82.7 and 76.2 Shore D, respectively. The PLA/PEG/GO showed the highest MFI, 73.1 g/10 min, while PLA/PEG/mCNTs recorded 70.5 g/10 min, both at 1.5 wt.% nanofiller loading. This proved that the PEG is useful in reducing the brittleness of nanocomposite. In further characterization, nanofiller at 1.5 wt.% of carbon-based loading was chosen for both melt and solution blending. The full exfoliation of CNTs and mCNTs in matrix observed from the X-ray Diffraction (XRD) analysis supported the excellent hardness and MFI properties. These nanocomposites also showed high thermal stability as obtained from Differential Scanning Calorimetry (DSC) and Thermogravimetric Analysis (TGA) studies compared with neat PLA. The morphology study by Field Emission Scanning Electron Microscopy (FESEM) analysis confirmed these findings through the existence of smooth fracture surface especially when PEG was loaded as an evidence of good distribution of nanofiller in matrix was established. In soil degradation analysis, neat PLA exhibited low weight loss rate after 6 months. The addition of GO and mCNTs increased the biodegradation rate of nanocomposites, compared with unmodified fillers. When further comparison was made, the PEG also slightly enhanced the degradation rate of nanocomposites. PLA/PEG/1.5 wt.% mCNTs prepared from melt blending was selected as the most outstanding nanocomposite with high performing in MFI, hardness and high thermal stability. This nanocomposite was among of the nanocomposites that has high biodegradable rate, a significant finding in order to reduce the waste removal problem of polymer nowadays. Design Expert Software was used to examine the effect of immersion condition on weight loss of nanocomposite. In hydrolytic study, the condition at 65 oC of 28 days’ immersion in hydrochloric acid (HCl) at pH 3 gave 22.53 % of maximum weight loss. In summary, the results obtained showed that the method in preparation of PLA nanocomposites influenced the properties of mechanical, rheological, thermal and rate of biodegradation due to the dispersion quality of nanofiller in PLA matrix.